ECB Monetary Policy and consequences in the European Monetary Union - Sánchez, Paola (Papeles de Europa, 2014)
The European Union debt crisis has questioned the institutional design of the European Monetary System (EMS). In 2011, one of the most influential authors, Werner Sinn, argued that the European Central Bank (ECB) was financing the current account deficits in the periphery countries and for this reason, the TARGET2 imbalances were dangerously increasing the risk in core countries. This paper considers that the TARGET2 imbalances have their roots in the interbank market paralysis and in the ECB role in the crisis, avoiding the financial system collapse. However, these imbalances are not a single problem but to reflect the political economy decisions. Sinn’s arguments hide a defence to austerity policies and the need to improve the competitiveness in the Southern countries and therefore the liabilities vis-à-vis the Euro-system.
Keywords: TARGET2; ECB; Monetary Policy; Euro-system; interbank market